2016
DOI: 10.1007/978-1-4939-4017-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation as a Quantitative Assay to Study Mammalian Male Germline Stem Cells

Abstract: In mammals, the activities of spermatogonial stem cells (SSCs) provide the foundation for continual spermatogenesis throughout a male's reproductive lifetime. At present, the defining characteristics of SSCs and mechanisms controlling their fate decisions are not well understood. Transplantation is a definitive functional measure of stem cell capacity for male germ cells that can be used as an assay to provide an unequivocal quantification of the SSC content in an experimental cell population. Here, we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Here we found that ID4-EGFP Bright spermatogonia are enriched in the testis following WIN 18,446 treatment, suggesting an increased number of spermatogonia with stem cell potential, a possibility we confirmed by transplantation. Taken together, flow cytometry and transplantation analyses suggest that some ID4-EGFP Mid spermatogonia still retain regenerative capacity consistent with the proposal by Helsel et al, 2017 that ID4-EGFP levels are proportional to SSC potential.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Here we found that ID4-EGFP Bright spermatogonia are enriched in the testis following WIN 18,446 treatment, suggesting an increased number of spermatogonia with stem cell potential, a possibility we confirmed by transplantation. Taken together, flow cytometry and transplantation analyses suggest that some ID4-EGFP Mid spermatogonia still retain regenerative capacity consistent with the proposal by Helsel et al, 2017 that ID4-EGFP levels are proportional to SSC potential.…”
Section: Discussionsupporting
confidence: 87%
“…Transplantation was performed as previously described (Helsel and Oatley, 2017). Recipients were C57BL6/JX129S1/svlmJ F1 hybrid mice treated with IP injection of busulfan (50mg/kg of body weight) at 6 weeks of age and recovered at least 6 weeks to ensure germ cell depletion (Brinster and Avarbock, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Donor mice for primary cultures of undifferentiated spermatogonia were male Rosa26-LacZ (Jax Mice, strain 002073) hybrids at P6–P8 or adult (3–4 months) ages. Recipients for transplantation analyses were either adult male W / W v mutants (Jax Mice, strain 000049) or F1 hybrids of a C57BL/6J (Jax Mice, strain 000664) × 129S1/svlmJ (Jax Mice, strain 002448) cross that were treated with busulfan to eliminate the endogenous germline, as described previously (Helsel and Oatley, 2017, Oatley and Brinster, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…A multitude of studies have demonstrated maintenance of heterogeneous undifferentiated spermatogonial populations in these conditions that are composed of a small number of SSCs and abundant non-stem cell progenitor spermatogonia (Kanatsu-Shinohara et al., 2003, Kanatsu-Shinohara et al., 2011, Kubota et al., 2004b, Oatley et al., 2009, Schmidt et al., 2011, Seandel et al., 2007, Takashima et al., 2015). Importantly, a robust transplantation assay is in place to directly assess the maintenance of SSC regenerative integrity in the primary cultures (Helsel and Oatley, 2017). For these reasons, cultures of mouse cells are an attractive platform for optimizing conditions that may be applicable to a wide range of other mammalian species including humans.…”
Section: Introductionmentioning
confidence: 99%
“…To conduct the experiments in a quantitative manner, we generated F1 hybrid males possessing Id4-eGfp and Rosa26-lacZ transgenes to serve as the source of donor germ cells. The Rosa26-lacZ transgene allows for colonies of donor-derived spermatogenesis within recipient testes to be clearly identified by blue staining and to be quantified visually (Brinster and Zimmermann, 1994;Helsel and Oatley, 2017). Because each colony is clonally derived from a single SSC (Nagano et al, 1999;Kanatsu-Shinohara et al, 2006), colony number is a direct measure of stem cell content in a transplanted cell population.…”
Section: Identification Of Id4-egfpmentioning
confidence: 99%